Branding Strategy Analysis of the Indonesian Book Information System (SIBI) Using the AISAS Approach - Wirasari, Ira; Fadhil, Indra; Justicia, Arunia; Sudibyo, Gina Suastika; Arif, Riksa; Fauzul, Aghnia (Jurnal Sosioteknologi, 2024)
Low literacy rates in childhood are a concern for the Indonesian government. More community activities on social media are demanding the digitization of teaching materials. Access to teaching materials is one factor in increasing children's literacy. The Indonesian government is continuously enhancing educational facilities, including the development of the SIBI platform, also known as the Indonesian Bookkeeping Information System, which offers free access to digital books. A branding strategy is needed to campaign and attract public attention to access the SIBI platform and try reading books with digital media. This research was conducted to analyze the branding strategy using the AISAS model. This research employs qualitative methods by gathering data through literature studies, observations, and interviews. This study demonstrates that the SIBI branding strategy has been running in accordance with the AISAS model branding theory and can attract the attention of users who are growing.